2021
DOI: 10.1016/j.chb.2020.106605
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of perceived body ownership in virtual reality-based teleoperation may backfire in the execution of high-risk tasks

Abstract: Guided by previous research on the role of embodiment in virtual environments, this study aimed to investigate the potential effects of using human-like (compared to robotic) virtual hands on work performances in the context of virtual reality (VR)-based teleoperation of high-risk machinery. A 2 × 2 mixed factorial design experiment ( N = 74), with the virtual hand representation as a within-subjects factor (robotic vs. human-like virtual hands) and the risk of danger as a between-subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Lastly, in a very recent study the so far positive relationship between ownership and performance was challenged by the notion of risk of danger in the context of VR-based machinery teleoperation (Shin et al, 2021). Participants performed pick and place tasks on a conveyor belt, during which a "raw material" had to be placed in a metal press machine for quick pressing (high risk) or slow pressing (low risk), using either a realistic hand or a robot hand.…”
Section: Ownership and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in a very recent study the so far positive relationship between ownership and performance was challenged by the notion of risk of danger in the context of VR-based machinery teleoperation (Shin et al, 2021). Participants performed pick and place tasks on a conveyor belt, during which a "raw material" had to be placed in a metal press machine for quick pressing (high risk) or slow pressing (low risk), using either a realistic hand or a robot hand.…”
Section: Ownership and Performancementioning
confidence: 99%
“…For example, Grechuta et al found clear positive correlations between body ownership and performance in various tasks in VR (Grechuta et al, 2017;Grechuta et al, 2019). In contrast, Shin et al found that greater body ownership may cause an increased risk perception, which in turn leads to degraded performance in pick-and-place tasks in VR (Shin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, it depends on the purpose people use VR. For example, if people consider the high-risk case in VR, it can make them activate the mechanism to avoid familiarizing themselves with negative stimuli [15].…”
Section: Introductionmentioning
confidence: 99%
“…The arm's visual human-likeness refers to the humanlikeness and appearance fidelity of the embodied objects such as a robotic hand. The more the object one is controlling is similar to the real body, the higher will be the operator's SoE (Mick et al, 2020;Shin et al, 2021).…”
mentioning
confidence: 99%